Acknowledging the divine benefactor : the second letter of Peter - Callan, Terrance (James Clarke & Co., 2015)
Acknowledging the Divine Benefactor' is a socio-rhetorical interpretation of the Second Letter of Peter. Using multiple interpretive perspectives and emphasising the pictorial dimensions of 2 Peter, Terrance Callan shows that the letter makes the following argument: since Jesus Christ has given his followers benefits, including the promise of sharing in divine nature, they need to make a proper return for these benefits by living virtuously; and this in turn will enable them to receive the fulfilment of the promise. The occasion of the letter is that Peter's death is near. He writes so the add.